Assembly area risk assessment methodology for post-flood evacuation by integrated neutrosophic AHP-CODAS - Sahmutoglu, Irem; Taskin, Alev; Ayyildiz, Ertugrul (SPRINGER, 2023)
Floods are one of the natural disasters that affect human life materially and morally. There are various measures to prevent flood damage. The evaluation of flood risk and assembly points is of great importance for flood risk preparation and disaster mitigation measures. This study presents a two-stage framework with a multi-criteria decision-making (MCDM) technique for flood and assembly point risk assessment problems. First of all, with a detailed literature review, the main and sub-criteria affecting the flood and assembly points are determined. Each criterion is evaluated with expert opinion. Then, the importance weights of the criteria are determined with the Interval-Valued Neutrosophic Analytical Hierarchy Process (IVN-AHP) methodology. The ranking of the twelve assembly points in Bartin according to their risks is obtained by the Interval-Valued Neutrosophic Combinative Distance-based Assessment (IVN-CODAS) method. The proposed risk assessment methodology is applied to the Merkez district of Bartin, Turkey, which is frequently exposed to floods. In this context, a risk assignment hierarchy consisting of 6 main criteria as Topographic, Access, Hydrological, Sociological, Humanitarian Aid and Infrastructure and a total of 24 sub-criteria is constructed. The most important main criterion is determined as Topographic. Although 'Topographic' is the most important main criterion, considering that there is no significant difference between this criterion and the others, it is suggested that each criterion should be considered when determining the location of an assembly point. The results demonstrate that the most important sub-criterion is Proximity to flood risk area with a final weight of 0.076 among 24 criteria. The result of the proposed methodology is tested by sensitivity analysis. A comparative analysis is also done to verify the efficiency of the proposed methodology. The proposed integrated methodology is intended to be a useful tool for disaster risk assessments and to guide decision makers.
Keywords: Assembly point; Flood risk; Interval-valued neutrosophic numbers; AHP; CODAS; ANALYTICAL HIERARCHY PROCESS; DECISION-MAKING APPROACH; SUSCEPTIBILITY ASSESSMENT; CRITERIA; SELECTION; Geology; Meteorology & Atmospheric Sciences; Water Resources